Development and validation of new multiresidue method for the determination of multiclass pesticide residue using LCMS/MS in onions - Vojislava Bursić (Proceedings of the International Symposium on Analytical and Environmental Problems, 2016)
The LC-MS/MS was used in the ESI+ mode. The method was set for the detection of six multiclass pesticides in a single injection. The validation procedure for the method was in accordance with SANTE /11945/2015and it was carried out using blank onion samples spiked with a pesticide mix solution at four levels: 0.01, 0.02, 0.1 and 0.2 μg/mL, with carbofuran– D3 as the internal standard. The linearity of the method was investigated in the range from 0.01 to 0.20 mg/kg. The obtained R2 values for all investigated pesticides (formetanate hydrochloride, spirotetramat, spinosad, dimethomorph, metalaxyl-Mand mandipropamid)were higher than 0.99.The recoveries ranged from96.2 to 101.45 with the precision lower than 8.00%. The LODs were calculated using the Agilent MassHunter B.04.00 software, and the LOQs were experimentally set at 0.01 mg/kg.